Bulgaria Spending Review : Improving Efficiency and Effectiveness of Waste Management Spending - World Bank (World Bank, Washington, DC, 2019)
In 2016, the Government of Bulgaria (GoB) decided to initiate spending reviews (RS) to improve the efficiency and effectiveness of its spending in the context of a moderate fiscal consolidation process. Although Bulgaria has one of the lowest overall spending in the European Union (EU), spending outcomes lag those of other EU member states. In the case of waste management, Bulgaria spends the most among comparable EU countries, but outcomes could be significantly improved. Still a large part (48 percent in 2016 ) of municipal solid waste generated is landfilled even though waste management infrastructure is under development. To help address these challenges the Ministry of Finance (MoF) requested analytical and advisory support from the World Bank. Such support was intended to identify spending pressures and potential efficiency and effectiveness gains in waste management. In contrast to most spending reviews, where saving targets are identified upfront and the primary objective is to find ways of reducing the budget, the primary objective of this review is to increase performance and use any savings derived from efficiency gains for additional priority spending on waste management. A secondary objective is for this SR to help increase the transparency of spending on waste management, as information on spending categories by activity and municipality has not been analyzed until now.